Managing drug-resistant epilepsy: challenges and solutions - Dalic L (Dove Medical Press, 2016)
Linda Dalic,1 Mark J Cook2,3 1Department of Neurology, Austin Health, 2St Vincent’s Hospital, Centre for Clinical Neurosciences and Neurological Research, 3Department of Medicine, The University of Melbourne, Melbourne, Australia Abstract: Despite the development of new antiepileptic drugs (AEDs), ~20%–30% of people with epilepsy remain refractory to treatment and are said to have drug-resistant epilepsy (DRE). This multifaceted condition comprises intractable seizures, neurobiochemical changes, cognitive decline, and psychosocial dysfunction. An ongoing challenge to both researchers and clinicians alike, DRE management is complicated by the heterogeneity among this patient group. The underlying mechanism of DRE is not completely understood. Many hypotheses exist, and relate to both the intrinsic characteristics of the particular epilepsy (associated syndrome/lesion, initial response to AED, and the number and type of seizures prior to diagnosis) and other pharmacological mechanisms of resistance. The four current hypotheses behind pharmacological resistance are the “transporter”, “target”, “network”, and “intrinsic severity” hypotheses, and these are reviewed in this paper. Of equal challenge is managing patients with DRE, and this requires a multidisciplinary approach, involving physicians, surgeons, psychiatrists, neuropsychologists, pharmacists, dietitians, and specialist nurses. Attention to comorbid psychiatric and other diseases is paramount, given the higher prevalence in this cohort and associated poorer health outcomes. Treatment options need to consider the economic burden to the patient and the likelihood of AED compliance and tolerability. Most importantly, higher mortality rates, due to comorbidities, suicide, and sudden death, emphasize the importance of seizure control in reducing this risk. Overall, resective surgery offers the best rates of seizure control. It is not an option for all patients, and there is often a significant delay in referring to epilepsy surgery centers. Optimization of AEDs, identification and treatment of comorbidities, patient education to promote adherence to treatment, and avoidance of triggers should be periodically performed until further insights regarding causative pathology can guide better therapies. Keywords: drug-resistant epilepsy, pharmacoresistant, management, review